Effect of Hybridization Approach on Mechanical Performance of Jute-hemp/epoxy Hybrid Composite Laminates. Issue 16 (28th November 2022) - Ahmad, Ahsan; Moeed, Abdul; Tariq, Asra; Nawab, Yasir; Farooq, Muhammad Umer; Umair, Muhammad
ABSTRACT: In this study, four-layered hybrid jute-hemp/epoxy composite laminates were fabricated by increasing and decreasing the number of layers of both jute and hemp reinforcements during stacking. Two jute(J) and hemp(H) controlled i.e., A(0J4H) and E(4J0H) and three jute(J)-hemp(H) hybrid i.e., B(1J3H), C(2J2H) and D(3J1H), composite laminates were fabricated. Composites were fabricated by hand layup followed by compression molding technique, and different mechanical tests (tensile, flexural, Charpy and drop weight impact) were performed. Results showed that hemp/epoxy laminate A(0J4H) revealed the highest tensile, flexural, Charpy and drop weight impact testing results followed by three hybrid composite laminates i.e., B(1J3H), C(2J2H) and D(3J1H), respectively. In hybrid composites, trend of mechanical properties was increased with the increase in number of plies of hemp reinforcements. The least mechanical testing results were presented by the E(4J0H) laminate because it was comprised of only four plies of jute reinforcement. Drop weight impact tested samples revealed that hybrid laminates C(2J2H) showed the least damage area in comparison with others due to the presence of equal number of jute and hemp plies. Also, within the same time duration, the highest force value was achieved along with less displacement by A(0J4H) laminate during drop weight impact test.